Problem-based Language Learning and Teaching An Innovative Approach to Learn a New Language - Ansarian, Loghman (SpringerBriefs in Education,, 2018)
This book investigates how problem-based learning can be implemented in language classes and how it can bring about a change in language learners' understanding of the foreign language. Based on empirical evidence, it provides readers with the theoretical background of this interdisciplinary approach in education, discusses the challenges that language teachers might encounter while implementing this approach in language classes, and offers procedures for employing the method. It also clarifies the difference between collaborative learning and problem-based learning in which certain dynamics are at work. It is of interest to researchers and instructors in cognitive learning, task-based language teaching, and content-focused courses.